The challenge for economic and social welfare: maintaining the balance between employment and wage recovery. - Peñaloza Méndez, Andrés (Revista Internacional de Salarios Dignos, 2020)
Strictly speaking, the recovery of formal jobs in the private sector began last July. Insured workers with an associated salary, which represent 99% of those insured by the Mexican Social Security Institute (IMSS), increased by 16,835 with respect to last month, a positive monthly variation of 0.1%. If there is no pandemic rebound, it is possible to begin to reverse the 1,111,888 jobs lost during March-June in this segment, which has fallen by 4.4% in comparison with the previous year. Regarding the other segment of IMSS members, equivalent to 1%, the insured workers without an associated salary, where the loss of jobs in July was concentrated: -20,742, a monthly variation of -15.1%, is due to seasonal falls, so the health emergency is not the main cause. It is worth mentioning that this segment of workers includes 30 (sugar cane producers), 35 (employers who are individuals with workers at their service), 43 (voluntary incorporation of the field into the obligatory regime), 44 (independent) and whose registered salary is not that of a real income received but rather a referential salary equal to the minimum wage.